Analyzing behavioral bias in gamblers using a game theoretical model - Chew, Jee Yuen (2013)
Problem gambling is an issue in many parts of the world and it has brought about negative impacts to the society. Problem gamblers usually start off as casual gamblers but they became addicted overtime. One common sign of problem gambling is the inability of gamblers to walk away once they start to gamble and this is related to a behavioral bias known as escalation of commitment. In order to curb the rise in problem gambling rates, it is imperative for us to understand the behaviors of problem gamblers and look into the behavioral bias exhibited by them. In this paper, we specifically look at the behavioral bias of escalation of commitment in relation to problem gamblers’ choice of betting amount, their tolerance level to losing streaks and their tendencies to chase losses and loan money. Our results showed that there is a strong and significant relationship between the severity of problem gambling, through the calculation of Problem Gambling Severity Index (PGSI) scores, and the extent of behavioral bias that participants exhibit. This suggests that participants with higher PGSI scores exhibit more behavioral bias. Moreover, we established that as a casual gambler exhibits more bias, the probability of him or her in becoming a problem gambler increases. Results from this research provide insights into how future policies and treatments targeted at problem gamblers can be shaped. Behavioral tools can be incorporated to encourage problem gamblers to stay away from gambling by increasing personal awareness of their behavioral bias.